1995
DOI: 10.1007/s001250050324
|View full text |Cite
|
Sign up to set email alerts
|

Long-term comparison of human insulin analogue B10Asp and soluble human insulin in IDDM patients on a basal/bolus insulin regimen

Abstract: SummaryRecombinant DNA technology allows the production of insulin analogues with faster absorption rates from subcutaneous tissue as compared to soluble human insulin. The human insulin analogue B10Asp (mono/dimeric) is absorbed twice as fast as soluble human insulin (hexameric). A double blind, randomised crossover study with a 1-month run-in period and two 2-month treatment periods was performed in 21 male insulin-dependent diabetic (IDDM) patients aged 18-40 years in order to compare the metabolic control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1996
1996
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…11,12 Despite this theoretical superiority of SAI analogues over regular insulin, it is unclear whether the efficacy of SAI analogues in the treatment of diabetic patients is better than with human regular insulin. 13,14 Treatment with the 2 SAI analogues available on the market is currently promoted with purported advantages with respect to metabolic control, reduced incidence of hypoglycemic episodes, and improved quality of life for patients with diabetes mellitus. We performed a systematic review and meta-analysis according to the QUOROM statement 15 of randomized controlled trials with the aim of providing information on glucose control, hypoglycemia, quality of life, and diabetes-specific complications of SAI analogues compared with regular insulin.…”
mentioning
confidence: 99%
“…11,12 Despite this theoretical superiority of SAI analogues over regular insulin, it is unclear whether the efficacy of SAI analogues in the treatment of diabetic patients is better than with human regular insulin. 13,14 Treatment with the 2 SAI analogues available on the market is currently promoted with purported advantages with respect to metabolic control, reduced incidence of hypoglycemic episodes, and improved quality of life for patients with diabetes mellitus. We performed a systematic review and meta-analysis according to the QUOROM statement 15 of randomized controlled trials with the aim of providing information on glucose control, hypoglycemia, quality of life, and diabetes-specific complications of SAI analogues compared with regular insulin.…”
mentioning
confidence: 99%
“…For example, previous studies have shown that the insulin analog [B10-Asp]-insulin caused mammary tumors in rats (Jorgensen, Dideriksen, and Drejer 1992). [B10-Asp]-insulin has, however, only been tested for 2 months in patients with type 1 diabetes, but has never been used for long-term treatment (Nielsen et al 1995). One possible explanation for the carcinogenic activity of [B10-Asp]-insulin is that it is characterized by an increased level of binding to the insulin-like growth factor-1 (IGF-1) receptor as demonstrated by in vitro binding studies.…”
mentioning
confidence: 99%
“…However, the present study has also clearly demonstrated that an appropriate dose of NPH can be chosen to prevent the preprandial deterioration of glucose levels noted with the lispro regimen (21)(22)(23)(24). We chose a dose based on the 30% reduction in lispro dose at both the current (lunch) and the next (dinner) meal, thus keeping the total insulin dose equivalent for experimental purposes and resulting in an approximate 50:50 mixture of lispro:NPH at lunchtime.…”
Section: Blood Intermediary Metabolitesmentioning
confidence: 62%